Analysis of the Classification of Crime of Sexual Intercourse with a Dead Body (Necrophilia) according to Anil Aggarwal in Indonesian Criminal Law - Isnawan, Fuadi (JURNAL USM LAW REVIEW, 2024)
This research critically examines Indonesian criminal law in addressing necrophilia's various manifestations, emphasizing the protection of deceased dignity and human rights. Using normative legal analysis, the study reveals that Indonesian criminal law provides partial coverage for necrophilia cases. Role Player necrophilia is addressed by Articles 6b and 12 of the TPKS Law, focusing on victim dignity and perpetrator sanctions. Romantic necrophilia, involving exhumation or corpse concealment, may fall under Criminal Code Articles 180 and 181, aimed at protecting the sanctity of the deceased. Necrophiliac Fantasizers, though not explicitly penalized, raise concerns due to the potential transition from fantasy to criminal acts. Tactile necrophilia is punishable under Articles 6b and 6c of the TPKS Law when physical abuse of corpses occurs. Additionally, Fetishistic necrophiles and Necromutilomaniacs who exploit corpses are subject to Criminal Code Articles 180 and 181. The findings indicate a need for legal reform, as current laws fail to comprehensively cover all necrophilia types, especially Romantic necrophilia and Necrophiliac Fantasizers. Furthermore, Homicidal and Exclusive necrophiles, committing extreme offenses, fall under Articles 338, 339, and 340, along with Article 6b and 180, addressing severe harm, murder, and corpse exploitation. This study’s novelty lies in categorizing necrophilia types within Indonesian law, highlighting gaps in legal protections. It recommends targeted legal amendments to ensure all forms of necrophilia are adequately recognized and prosecuted, thereby strengthening ethical and societal standards.